High School Students Are a Target Group for Fight against Self-Medication with Antimalarial Drugs: A Pilot Study in University of Kinshasa, Democratic Republic of Congo - Ramsès Kabongo Kamitalu; Michel Ntetani Aloni (Journal of Tropical Medicine)
Aim. To assess the self-medication against malaria infection in population of Congolese students in Kinshasa, Democratic Republic of Congo (DRC). Methods. A cross-sectional study was carried out in University of Kinshasa, Kinshasa, Democratic Republic of Congo. Medical records of all students with malaria admitted to Centre de Santé Universitaire of University of Kinshasa from January 1, 2008, to April 30, 2008, were reviewed retrospectively. Results. The median age of the patients was 25.4 years (range: from 18 to 36 years). The majority of them were male (67.9%). Artemisinin-based combination treatments (ACTs) was the most used self-prescribed antimalarial drugs. However, self-medication was associated with the ingestion of quinine in 19.9% of cases. No case of ingestion of artesunate/artemether in monotherapy was found. All the medicines taken were registered in DRC. In this series, self-prescribed antimalarial was very irrational in terms of dose and duration of treatment. Conclusion. This paper highlights self-medication by a group who should be aware of malaria treatment protocols. The level of self-prescribing quinine is relatively high among students and is disturbing for a molecule reserved for severe disease in Congolese health care policy in management of malaria.